Moving from Raman Spectroscopy Lab towards Analytical Applications: A Review of Interlaboratory Studies - Elena-Andreea Rusu; Monica Baia (Instruments, 2023)
Is Raman spectroscopy applicable for analytical purposes? Although Raman spectroscopy is a commonly used technique for analyzing sample characteristics and has numerous benefits, it still has several significant limitations that hinder the current tendency to produce the same results regardless of location, equipment, or operator. Overcoming these drawbacks may help to further the development of personalized medicine, diagnosis and treatment, the development of work protocols, and the pursuit of consistent and repeatable performance across all fields. Interlaboratory studies are currently the best way to do this. In this study, we reviewed the interlaboratory studies on Raman spectroscopy conducted to highlight the importance of moving to quantitative analysis in controlled environments. The advantages of Raman spectroscopy, including its high molecular specificity, short spectrum acquisition time, and excellent component identification capabilities, were clearly stated in all experiments. The Raman spectroscopy lab is taking small steps toward analytical applications by figuring out how to accurately predict concentrations in the relevant range of concentrations, developing and verifying the technology, and producing homogenous samples for those investigations.